Evaluation of the Financial Management Capacity of the Food Firms Listed on the Hanoi Stock Exchange - Duc Tai Do (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
The study investigates financial management capacity of food firms listed on the Hanoi stock exchange (HNX). The study employs a set of aggregated data from 15 food firms listed on the HNX. At the same time, the study also receives comments from experts experienced in the research field. We have performed some descriptive statistics, compared and correlation analysis with support by Stata13 software to evaluate and measure financial management capacity of food firms listed on the HNX through the financial indicators, including (i) accounts receivable turnover ratio (FMC1); (ii) average collection period (FMC2); (iii) accounts payable turnover (FMC3) and (iv) average payment period (FMC4). The results show that there is a difference in financial management capacity of food firms listed on the HNX. Firms with 10% or more foreign ownership account for a relatively low proportion of these enterprises.